2018
DOI: 10.1111/1471-0528.15059
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant use during pregnancy and the risk of attention‐deficit/hyperactivity disorder in the children: a meta‐analysis of cohort studies

Abstract: Antidepressant use during pregnancy may be not associated with ADHD in the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…odds, hazard, or relative risk ratios) ranging from approximately 1.0–2.5 (Table ; Andalib et al., ; Brown, Hussain‐Shamsy, Lunsky, Dennis, & Vigod, ; Kaplan, Keskin‐Arslan, Acar, & Sozmen, ; Kaplan, Keskin‐Arslan, Acar, & Sozmen, ; Kobayashi, Matsuyama, Takeuchi, & Ito, ; Man et al., ; Mezzacappa et al., ; Morales et al., ; Zhou, Li, Ou, & Li, ).The meta‐analyses on ADHD have generally reported pooled point estimates (i.e. odds or relative risk ratios) of about 1.5 (Table ; Jiang, Peng, Zhang, & Ruan, ; Man et al., ; Morales et al., ).…”
Section: Observational Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…odds, hazard, or relative risk ratios) ranging from approximately 1.0–2.5 (Table ; Andalib et al., ; Brown, Hussain‐Shamsy, Lunsky, Dennis, & Vigod, ; Kaplan, Keskin‐Arslan, Acar, & Sozmen, ; Kaplan, Keskin‐Arslan, Acar, & Sozmen, ; Kobayashi, Matsuyama, Takeuchi, & Ito, ; Man et al., ; Mezzacappa et al., ; Morales et al., ; Zhou, Li, Ou, & Li, ).The meta‐analyses on ADHD have generally reported pooled point estimates (i.e. odds or relative risk ratios) of about 1.5 (Table ; Jiang, Peng, Zhang, & Ruan, ; Man et al., ; Morales et al., ).…”
Section: Observational Studiesmentioning
confidence: 99%
“…Four meta‐analyses, which included overlapping studies, found statistically significant associations between antidepressant use before pregnancy and ASD (Table ; Kaplan, Keskin‐Arslan, Acar, et al., ; Mezzacappa et al., ; Morales et al., ; Zhou et al., ), and three meta‐analyses also including overlapping studies found statistically significant associations between antidepressant use before pregnancy and ADHD (Table ; Jiang et al., ; Man et al., ; Morales et al., ; Table includes results from individual studies). These associations were of similar magnitude as associations reported for use during pregnancy.…”
Section: Observational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the meta‐analyses included data on TCAs. The number of meta‐analyses evaluating individual neonatal outcomes was as follows: autism spectrum disorders, 10 15‐24 ; ADHD, 4 21,23,31,32 ; preterm birth, 4 25‐28 ; persistent pulmonary hypertension, 3 14,33,34 ; low birth weight, 2 25,29 ; and spontaneous abortion, 2 28,30 …”
Section: Resultsmentioning
confidence: 99%
“…All meta‐analyses found that first‐trimester exposure was significantly associated with the risk of ADHD (OR/RR/HR for any antidepressant, 1.37‐1.39; HR/OR for SSRIs, 1.52‐1.75). The increased risk of ADHD in children of women using any antidepressant during the second trimester 31 or second/third trimester 32 was reported in 1 meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%